Is It an Outbreak of Health Care-Associated Infection? An Investigation of Binocular Conjunctival Congestion After Laparoscopic Cholecystectomy Was Traced to Chitosan Derivatives - Liu, Sidi; Huang, Xun; Fu, Chenchao; Dou, Qingya; Li, Jie; Feng, Xuelian; Mo, Yang; Meng, Xiujuan; Zeng, Cui; Wu, Anhua; Li, Chunhui (Frontiers in Medicine, 2022)
Background: From May 6 to May 23, 2019, 24 (80.00%) patients who underwent laparoscopic cholecystectomy (LC) developed binocular conjunctival congestion within four to eight hours after their operation in the day ward of a teaching hospital. Methods: Nosocomial infection prevention and control staff undertook procedural and environmental investigations, performed a case–control retrospective study (including 24 cases and 48 controls), and reviewed all lot numbers of biological material products to investigate the suspected outbreak of health care–acquired infection. Findings: Initially, an outbreak of health care–acquired infection caused by bacteria was hypothesized. We first suspected the membranes that covered patients' eyes were cut using nonsterile scissors and thus contaminated, but they failed to yield bacteria. In addition, both corneal and conjunctival fluorescein staining results were negative in case–patients and isolated bacteria were ubiquitous in the environment or common skin commensals from 218 samples from day surgery and the day ward. Hence, we considered a noninfectious factor as the most likely cause of the binocular conjunctival congestion. Then, we found that case–patients were more likely than LC surgery patients without binocular conjunctival congestion to be exposed to biological materials in a retrospective case–control study. When we reviewed lot numbers, duration of use, and the number of patients who received four biological material products during LC in the day ward, we found that the BLK1821 lot of a modified chitosan medical film was used concurrently to when the case aggregation appeared. Finally, we surmised there was a correlation between this product and the outbreak of binocular conjunctival congestion. Relapse of the pseudo-outbreak has not been observed since stopping usage of the product for six months. Conclusion: A cluster of binocular noninfectious conjunctival congestion diagnosed after LC proved to be a pseudo-outbreak. We should pay more attention to adverse events caused by biomaterials in hospitals.